Study on the chemical constituents of Urena lobata growing in Viet Nam - Quan, Pham Minh; Van, Tran Thi Hoai; Lam, Do Tien; Phuong, Doan Lan; Ich, Cam Thi; Long, Pham Quoc; Minh, Pham Thi Hong (Vietnam Journal of Science and Technology, 2019)
Urena lobata L. is used in Vietnamese traditional medicine for the treatment of several diseases. Tree roots are used to treat rheumatism, dysentery, poor digestion, flu, tonsils, malaria, asthma, goiter. Flowers are used to treat chickenpox, fever, and mental disorders. Branches, leaves or whole trees used to treat injuries bruises, rheumatism, mastitis, bites. Phytochemical investigation of the n-hexan and ethyl acetate extract of Urena lobata L. led to the isolation of β-sitosterol (1), β-sitosterol-3-O-β-D-glucopyranoside (2), a-acetylamino-phenylpropyl a-benzoylamino-phenylpropanoate (3), quercetin (4), and trans-tiliroside (5). Their chemical structures were determined by spectroscopic methods including MS, 1D, 2D NMR and comparing with those reported in previous papers. Two compounds 3, 5 were isolated for the first time from Urena lobata plant.